Transformation of the farming segment Of the aquaculture value chain in Bangladesh - Ali, Hazrat; Belton, Ben; Haque, Md. Mahfuzul; Khondker, Murshed-E-Jahan (WorldFish, 2024)
Aquaculture is a highly dynamic and rapidly growing sub-sector in the global food system, including Bangladesh. Bangladesh is the fifth largest aquaculture producing country in the world (FAO, 2022) and production has increased 20 times over the past 3 decades (DoF, 2022). The aquaculture sector has experienced significant growth, diversification, and technological innovations, indicating a noticeable shift toward more intensive cultivation techniques. However, yet very little is known about the characteristics of the dynamic and rapidly growing aquatic food value chain in Bangladesh. These gaps make it difficult to plan and manage aquaculture development or design appropriate investments, policies and effective interventions. Considering all these aspects collectively, comprehensive stacked survey-based research was conducted in aquatic food production segment considering the dynamic of transformation structure, conduct and performance.